Ask Iwata words of wisdom from nintendo's legendary ceo - Viz Media (San Francisco Viz Media, 2021)
Satoru Iwata was the global president and CEO of Nintendo and a gifted programmer who played a key role in the creation of many of the world?s best-known games. He led the production of innovative platforms such as the Nintendo DS and the Wii, and laid the groundwork for the development of the wildly successful Pokm̌on Go game and the Nintendo Switch. Known for his analytical and imaginative mind, but even more for his humility and people-first approach to leadership, Satoru Iwata was beloved by game fans and developers worldwide.
Keywords: Leadership